Pressure measurement algorithm of LPG leakage using MQ6 sensor and GSM SIM900 for smart home - Suhartono, Suhartono; Suhadi, Iwan (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2021)
Liquid Petroleum Gas (LPG) has a drawback in its use that it is very prone to cause fires because it is a hydrocarbon in the form of propane and butane. LPG storage must also use a strong cylinder and has no leakage. If the gas storage cylinder leaks, it will easily cause fire and explode when it is used. LPG must meet several particular criteria in terms of safety, so it does not damage the equipment used and can be efficient in its use. A gas leak detection system is required to reduce the risk of material and life loss due to gas cylinder leaks, which can later be used as a safety system or warning of gas leaks. The users can quickly response to gas leaks around them. The warning given can be a short message or an alarm as a reminder to the users. The purpose of this research is, first, to create an LPG gas leak pressure measurement algorithm using the MQ6 sensor and GSM SIM 900A for a Smart home. The second is to design an Arduino-based gas leak notification through an SMS Gateway. The method used in this study is experimental. This is a method that is generally used in laboratory research. The second is the prototype method, in which the device changes are carried out many times until the goal of the device to be developed is achieved. The research results are the first to produce an algorithm for measuring LPG gas leakage pressure using the MQ6 sensor, which can be installed in Smart home, testing this algorithm using a board on the Arduino microcontroller, which is connected directly to the MQ6 sensor as an input medium. After the algorithm is embedded to measure the gas leak pressure on the MQ6 sensor, it works as a sensor that only detects LPG, propane, butane and its types explicitly. In the results of trials that have been carried out by going through 4 stages of testing this detector, it will be more optimal to detect gas leaks at a distance of 5 cm. The second is to generate Arduino-based gas leak notification information using an SMS Gateway. This tool is also equipped with a GSM SIM 900A module that functions as an SMS gateway so that if a gas leak occurs, the GSM SIM 900A can be a communicator among the user's mobile devices to provide information via SMS. The better the quality of the available network, the faster the notification will be sent.